Agitated behaviors among elderly people with dementia living in their home in Taiwan - Huang HL (Dove Medical Press, 2018)
Huei-Ling Huang,1,2 Yea-Ing L Shyu,1,3–5 Wen-Chuin Hsu6 1Department of Gerontological Care and Management, Chang Gung University of Science and Technology, Taoyuan, Taiwan; 2Nursing Department, Taoyuan Chang Gung Memorial Hospital, Taoyuan, Taiwan; 3School of Nursing, College of Medicine & Healthy Aging Research Center, Chang Gung University, Taoyuan, Taiwan; 4Department of Orthopedic Surgery, Linkou Chang Gung Memorial Hospital, Taoyuan, Taiwan; 5Department of Nursing, Kaohsiung Chang Gung Memorial Hospital, Kaohsiung, Taiwan; 6Chang Gung Dementia Center, Department of Neurology, Chang Gung University and Memorial Hospital, Taoyuan, Taiwan Background/aims: Limited research has been conducted on agitated behavior in Taiwan and dementia among community-dwelling elderly. Therefore, this study focused on community elderly with dementia and a factor analysis of an inventory of their agitated behaviors was conducted.Patients and methods: Participants (N=221) completed the Chinese Cohen-Mansfield Agitation Inventory, community form. Item analysis and exploratory factor analysis assessed reliability, validity, and the underlying factor structure.Results: Five factors were extracted and accounted for 44.53% of the total variance. This study classified agitated behaviors into 5 main subtypes: physically agitated behaviors, destructive behaviors, verbally agitated behaviors, handling things behavior, and aggressive behaviors.Conclusion: The results indicate that differences in the agitated behavior of elderly with dementia exist with respect to cultural background and setting. This novel research and its findings serve as a reference for assessing the agitated behaviors of elderly with dementia living in their homes. Applications may exist for other countries with Chinese/Taiwanese populations. Keywords: agitation, aggressive behavior, behavioral problem, caregiver, factor analysis, dementia